The Status quo and way forwards on the development of Tibetan medicine and the pharmacological research of tibetan materia Medica. (May 2020) - Fu, Ke; Xu, Min; Zhou, You; Li, Xiaoli; Wang, Zhang; Liu, Xianwu; Meng, Xianli; Zeng, Yong; Zhang, Hai
Graphical abstract: Abstract: Tibetan medicine (TM), the second largest traditional Chinese medicine system in China, boasts a long history and an integrated theoretical system. It abounds with classical medical works constituing a unique corpus of Tibetan materia medica (TMM). China has now conceived a modern education system of TM, and Tibetan medical hospitals at different levels have been set up. Many enterprises are granted the privileges to produce preparations of TM in compliance with Good Manufacturing Practices (GMP) regulations. However, there still exist unsolved issuess in TMM research as to the mechanism of action and the active constituents of TMM which are now been tackled through pharmacology and modern science and technology. Up till now, the mechanism of action and the active constituents of 141 medicines as well as 230 preparations of TM have been preliminarily revealed. This paper reviews in detail the development of TM and the status quo of TM's pharmacological research, in hope of serving a reference value for the promotion of the modernization of TM and understanding of TM among the medical scholars.